Hypoxia inducible factors regulate infectious SARS-CoV-2, epithelial damage and respiratory symptoms in a hamster COVID-19 model. - Peter A C Wing; Maria Prange-Barczynska; Amy Cross; Stefania Crotta; Claudia Orbegozo Rubio; Xiaotong Cheng; James M Harris; Xiaodong Zhuang; Rachel L Johnson; Kathryn A Ryan; Yper Hall; Miles W Carroll; et al. (PLoS Pathogens)
Understanding the host pathways that define susceptibility to Severe-acute-respiratory-syndrome-coronavirus-2 (SARS-CoV-2) infection and disease are essential for the design of new therapies. Oxygen levels in the microenvironment define the transcriptional landscape, however the influence of hypoxia on virus replication and disease in animal models is not well understood. In this study, we identify a role for the hypoxic inducible factor (HIF) signalling axis to inhibit SARS-CoV-2 infection, epithelial damage and respiratory symptoms in the Syrian hamster model. Pharmacological activation of HIF with the prolyl-hydroxylase inhibitor FG-4592 significantly reduced infectious virus in the upper and lower respiratory tract. Nasal and lung epithelia showed a reduction in SARS-CoV-2 RNA and nucleocapsid expression in treated animals. Transcriptomic and pathological analysis showed reduced epithelial damage and increased expression of ciliated cells. Our study provides new insights on the intrinsic antiviral properties of the HIF signalling pathway in SARS-CoV-2 replication that may be applicable to other respiratory pathogens and identifies new therapeutic opportunities.